Discrepancy of MA Arifah Gowa Student's Speech toward Leech Language Politeness Principles - Idawati Idawati; Juwita Juwita; Rosdiah Salam (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
The research highlights the discrepancy between MA Arifah Gowa students' polite speech and Leech language politeness. This research is descriptive qualitative research. The data in this research are students' speech in words, clauses, and sentences that do not comply with the principles of language politeness based on Leech's theory. The results show that the discrepancy between students' speech and the principles of language politeness occurs in five maxims, including the maxim of wisdom, the maxim of generosity, the maxim of praise, the maxim of humility, and the maxim of agreement. Keywords: discrepancy, politeness principles, student language